1992
DOI: 10.1148/radiology.184.1.1319079
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the head and neck: evaluation with MR imaging and clinical-pathologic correlation in 27 patients.

Abstract: Twenty-seven adenoid cystic carcinomas (ACCs) of the head and neck in 27 patients were evaluated in a retrospective study based on findings at magnetic resonance (MR) imaging and pathologic and clinical examination. Clinical follow-up was obtained over a mean period of 6.3 years (range of follow-up, 3 months to 17 years); all patients underwent one to seven MR examinations. On T2-weighted images, lesions with low signal intensity corresponded to highly cellular tumors (solid subtype) with a poor prognosis; les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 0 publications
3
44
0
7
Order By: Relevance
“…Among low-grade MECs, tumours usually had a hyperintense area on T 2 weighted images, reflecting a cystic architectural pattern because of the existence of abundant mucin-secreting cells. A similar tendency of increased signal intensity on T 2 weighted images in lowergrade malignancies was reported for adenoid cystic carcinomas of the head and neck region [10]. In contrast with the previous literature that describes ill-defined margins on MR images as a predictor of high-grade malignancies [6][7][8][9], half of our low-grade MECs had illdefined margins on MR images, reflecting peritumoural inflammatory changes.…”
Section: Resultssupporting
confidence: 82%
“…Among low-grade MECs, tumours usually had a hyperintense area on T 2 weighted images, reflecting a cystic architectural pattern because of the existence of abundant mucin-secreting cells. A similar tendency of increased signal intensity on T 2 weighted images in lowergrade malignancies was reported for adenoid cystic carcinomas of the head and neck region [10]. In contrast with the previous literature that describes ill-defined margins on MR images as a predictor of high-grade malignancies [6][7][8][9], half of our low-grade MECs had illdefined margins on MR images, reflecting peritumoural inflammatory changes.…”
Section: Resultssupporting
confidence: 82%
“…In our patients the tumor extension was often underestimated during the preoperative staging by means of imaging techniques as compared with the intraoperative and histopathological findings, while Sigal et al 23 reported an overestimation of the tumor size (Fig. 1).…”
Section: Discussionmentioning
confidence: 47%
“…Perineural infiltration was noted on MR images in nine of 27 patients with ACC in a previous study [15]. Additionally, 11 of 80 cases of perineural tumor extension reported by Ballantyne [1] and 11 ot" 52 cases reported by Parker [5] were of adenoid cystic origin.…”
Section: 21 Adenoid Cystic Carcinomamentioning
confidence: 83%
“…Repeat recurrences and distant metastases occur over many years finally killing the patient. Repeat surgical excision and RT are the treatment of choice [15].…”
Section: 21 Adenoid Cystic Carcinomamentioning
confidence: 99%